Optimum Trp-Lys ratio in nursery pig diets (6-20 kg) - Daza A.; Gálvez J.F.; Cirera M.; Relandeau C. (Feed manufacturing in the Mediterranean region. Improving safety: From feed to food, 2001)
Tryptophan is an essential amino acid that belongs to the neutral aminoacids group. It is the fourth-limiting AA in growth and finishing diets, but in corn-soybean meal based diets it is the second-limiting AA after lysine. Besides being a factor in protein synthesis in the muscle, tryptophan is a precursor of serotonin, which is a part of the voluntary feed intake control system. There are several recommendations about the inclusion levels of tryptophan in nursery diets. For this reason, we have developed two experimental trials to analyse the response of nursery pigs (6 to 20 kg of BW) to diets supplemented with synthetic L-tryptophan. We tested responses to two different Trp/Lys ratios, two different NE levels and different crude protein concentrations.
3. Conference of Feed Manufacturers of the Mediterranean, 2000/03/22-24, Reus (Spain)